TEXT UNDERSTANDING BASED ON SEMANTIC RELATIONS BETWEEN SENTENCES - Hyeok Kong (Jurnal Informatika, 2015)
In this paper, we define event expression over sentences of natural language and semantic relations between events. Based on this definition, we formally consider text understanding process having events as basic unit.